Coeliac disease : proceedings of the Xth International Symposium on Coeliac Disease Paris, June 2-5, 2002 - Cerf-Bensussan, Nadine; Brousse, Nicole; Caillat-Zucman, S; Cellier, Christophe; Schmitz, Jacques (John Libbey Eurotext, 2003)
Proceedings of a symposium that focused on various aspects of celiac disease and a collection of works presented there. Intended for professional public.
Keywords: celiakie; gastroenterologie; Celiac Disease